Migration policy and integration in Quebec. A model based on the selection. - Garreta Bochaca, Jordi (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Canada, and specifically Quebec, is particularly interesting as well as other countries, because of the immigration they have received and because of the politics carried out to assimilate or to integrate those recently arrived. This article, product of a research stay in the country, presents the evolution of immigration in Quebec, the active policies carried out in the selection of immigrants starting from the concept of capacity of absorption, the selection criteria and the integration policies for this population which is considered necessary.